Effect of phage and host concentration on the inactivation of Escherichia coli O157:H7 on cooked and raw beef. (March 2015) - Hudson, JA; Billington, C; Wilson, T; On, SLW
A previously described phage infecting Escherichia coli O157:H7 was added to raw and cooked beef pieces at concentrations ranging from 10 1 –10 8 plaque forming units/cm 2 to either low (<100 CFU/cm 2 ) or high (10 4 CFU/cm 2 ) concentrations of host bacterial cells. Incubation for up to 24 h was performed at 5℃ and 24℃ to simulate refrigerated and room temperature storage/temperature abuse. Surviving bacteria were enumerated during the incubation period, with phages being counted at the first and last sampling times. Significant reductions of E. coli O157:H7 of the order of >4 log10 CFU/cm 2 at both temperatures could be achieved compared to phage-free controls. There was a trend for greater inactivation to occur with increasing phage concentration. While re-growth of surviving cells occurred in nearly all samples incubated for 24 h at 24℃, these conditions are not typical of those experienced by perishable foods. It was concluded that phages can be used to reduce the concentration of a bacterial pathogen on meat, but the concentration of phages needs to be high (>4–5 log10 plaque forming units/cm 2 ) for reductions to occur. A concentration of the order 8 log10 plaque forming units/cm 2 was needed to achieve a 4 log10 CFU/cm 2 reduction.